Design of hairpin filter using omega metamaterial substrate / Mohd Mahathir Suhaimi Shamsuri - Shamsuri, Mohd Mahathir Suhaimi
In this paper, a new innovation of omega structure as metamaterial substrate is implemented as a base construction of the hairpin bandpass filter has been proposed. A combination of RTD5880 and copper in omega structure has successfully performed the metamaterial behaviour. An investigation on the S-paramcters has been carried out to determine the negative permittivity of the metamaterial. The results from the proposed method has been analyzed and compared with the conventional hairpin bandpass filter in terms of insertion loss, return loss and size. Based on the simulation results, the presence of metamaterial has improved the performance for return loss, insertion loss and also reduces 21 times the size of the filter. The details of design for the proposed method arc presented and discussed.